Response of Giza 89 cotton cultivar to foliar application of ascorbic acid, gibberellic acid, phosphorus and potassium - El-Shazly, W. M. O.; El-Masri, M. F. (2003)
Two field experiments were carried out at Gemmeiza Agricultural Research Station, Gharbia Governorate during two seasons (2000 and 2001) to study the effect of foliar application with 1000 ppm ascorbic acid (AA), 100 ppm gibberellic acid (GA3), 2% calcium superphosphate (SP) and 2% potassium sulphate (KS) in comparison with untreated plots (spraying with water) as a control on leaf nutrients content, growth, earliness, seed cotton yield and yield components of Giza 89 cotton cultivar . The obtained results could be summarized as follows: 1-Foliar application of 1000 ppm AA, significantly increased leaf N, P, Ca, Fe, Zn and Mn contents as compared with the control treatment. However, this treatment insignificantly reduced leaf Cu content and increased leaf K and Mg contents compared with the control. This treatment significantly increased also plant height at harvest as compared with the control treatment or foliar feeding with P or K due to the number of main stem internodes increase, however, it reduced the average internode length. In addition, this treatment significantly increased numbers of total and open bolls/ plant, boll weight, seed cotton yield/ plant as well as/ feddan as compared with the control treatment. 2-Foliar application of 100 ppm GA3. significantly increased leaf macronutrients content (N, P, K, Ca and Mg) and leaf micronutrients content (Fe, Zn, Mn and Cu) as compared with the control treatment in both seasons. Also, this treatment significantly increased plant height at harvest as compared with the other tested treatments due to a significant increase in each of number of main stem internodes and/or internode length and number of fruiting branches/ plant. In addition, this treatment significantly increased numbers of total and open bolls/ plant in the first season and boll weight, seed cotton yield/ plant as well as/ feddan in both seasons as compared with the control treatment.
Includes reference.
Summary in Arabic.
1
Keywords: Cotton -- Composition; Cotton -- Growth; Cotton -- Varieties; Cotton -- Yields; Vitamin C; Gibberellic acid; Phosphorus; Potassium; Foliar feeding